Forecast five days ahead of the development of low pressure areas -and depressions /storms over the northern part of the Bay of Bengal during the southwest monsoon season - AHMED, M. N. (MAUSAM, 1978)
During the months of June, July, August and September, low pressure areas form with some regularity over the north Bay of Bengal. Most of these low pressure areas concentrate into depressions. Some of them even intensify into cyclonic storms. During the period from 1950 to 1975, 289 depressions/storms formed in the Bay. In this period 163 out of these 289 depressions/storms occurred during the S.W. monsoon m()nths June to September. The low pressure areas not reaching the stage of depressions have been left out of this account. The lows formed but not developed upto the stage of depressions have been accounted for the months June to September of the years 1971 to 1975. These lows and the depressions/storms were found occurring at regular intervals. A somewhat periodicity was maintained in their appearance. Pressure curves showing daily variations of pressure of Chittagong in the months June to September of the years 1971 to 1975 were made. The 0000 GMT mean sea level pressures were taken for the purpose. These curves were found in waveforms. Each wave has .the length, amplitude and period. The maximum and minimum of the pressures, i.e., wave crest and wave trough or the ridge and trough in the wave were found significant in view of the weather the place experienced during the period of the wave. The period of the wave was observed to be about 5 days. In case of a serious abnormality in any cyclonic circulation, the 'period' of. the particular wave was disturbed. The cyclonic circulations developing into lows of pressure and depressions in the Bay fitted fairly satisfactorily in the wave troughs. The coming wave crest and wave trough in the pressure curve may be worked out.